ANALISIS POLA DAN STRATEGI PENYEDIAAN PANGAN RUMAH TANGGA PETANI HUTAN KEMASYARAKATAN KABUPATEN LAMPUNG BARAT - Rini Nurindarwati; Sri Anna Marliyati; Yayat Heryatno (Food and Nutrition Society of Indonesia, 2008)
The main objective of this study is to provide information about food supplying pattern and strategy of Social Forestry’s farmer household. Thisstudy was conducted in October 2008 by using cross sectional study design. The sample was 90 Social Forestry’s farmer households. The data obtained by the research were household characteristics; food supplying pattern and strategy which analyzed descriptively and inferentially. More than half of the samples (78%) are small households with all farmers and housewives are in productive age. The income per capita per month of the sample is Rp509626. The food expenditure per capita per month is Rp213136, while non food expenditure per capita per month is Rp197851. The larger shares of food expenditure are utilized in food supplying of cereals (31.7%), vegetables and fruits (20.3%), and animal food (18.5%). Strategies for raising income conducted by the sample are searching supplementary income other than the main working field; conducting husbandry; and planting crops in garden. Saving is a strategy rarely conducted by the sample. Energy supplying of the sample for cereals, vegetables and fruits, oils and fats, sugar, and others are sufficient, while energy supplying for tubers, animal protein, legumes, and oily seed are not sufficient. The food supply is obtained by purchasing (70.8%), self production (28.2%), and other sources (0.4%).